2021
DOI: 10.1002/onco.13829
|View full text |Cite
|
Sign up to set email alerts
|

Homologous Recombination Deficiency: Cancer Predispositions and Treatment Implications

Abstract: Homologous recombination (HR) is a highly accurate DNA repair mechanism. Several HR genes are established cancer susceptibility genes with clinically actionable pathogenic variants (PVs). Classically, BRCA1 and BRCA2 germline PVs are associated with significant breast and ovarian cancer risks. Patients with BRCA1/BRCA2 PVs display worse clinical outcomes but respond better to platinum-based chemotherapies and PARP inhibitors, a trait termed as "BRCAness". With the advent of whole-exome sequencing and multigene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(73 citation statements)
references
References 138 publications
2
61
0
Order By: Relevance
“…Briefly, BRCA1 binds the site of DSB where it coordinates the repair mechanisms downstream [ 10 ]. BARD1 and BRIP1 both directly interact with BRCA1 mediating its function [ 11 ]. PALB2 dislodge BRCA2 onto DNA breaks, thus recruiting the RAD51 complex to stabilize the single strand DNA filament [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, BRCA1 binds the site of DSB where it coordinates the repair mechanisms downstream [ 10 ]. BARD1 and BRIP1 both directly interact with BRCA1 mediating its function [ 11 ]. PALB2 dislodge BRCA2 onto DNA breaks, thus recruiting the RAD51 complex to stabilize the single strand DNA filament [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…As such, pathogenic germline mutations in BRCA genes are associated with heritable cancer syndromes, predisposing to multiple solid tumors, including breast, ovarian, prostate and pancreatic cancer [6,7]. HRD tumor cells are characterized by a striking sensitivity to platinum chemotherapy and PARPi [4,5], but HRD and responsiveness to platinum chemotherapy/PARPi are not solely restricted to BRCA mutant tumors [8]. Mutations in some non-BRCA HR genes are also associated with HRD, although not all non-BRCA HR gene mutations confer the same clinical impact [9].…”
Section: Introductionmentioning
confidence: 99%
“…Homologous recombination deficiency (HRD) characterizes a unique set of cancers of various histologic origin leading to increased tumor mutation burden and special sensitivity to immune checkpoint inhibitors or to PARP inhibitors [ 18 ]. A study demonstrated that in breast cancer disseminated brain metastases genomic aberration-based HRD measures are significantly higher in metastases relative to their matched primary tumors suggesting that HR-deficient brain metastases might be more sensitive to PARP inhibitor treatment [ 19 ].…”
Section: Discussionmentioning
confidence: 99%